Recolonisation by ants and other invertebrates in rehabilitated coal mine sites near Collie, Western Australia - Van Schagen, John (1986)
This paper describes a study performed in a coal mine at Collie, Western Australia. Ten rehabilitated mine sites and 2 forest controls were investigated. The age of the rehabilitated plots ranged from 0.5 to 9.5 years. Soil form the rehabilitated areas had a higher impenetrability and higher bulk density value than the controls. Plant species richness and species richness were lower in the rehabilitated areas than in the unmined forest. Twenty nine species were found during the course of the study, of which 18 had colonised their rehabilitated plots. Ants' species richness was positively correlated with plant species richness, but negatively correlated with soil impenetrability. The time associated trend indicated that ant species richness increased with the age of rehabilitation. The recolonisation rate of the ants reflected that of certain other invertebrates. Data obtained in this study provide comparison with similar studies performed in bauxite, manganese and mineral sand mines, which relate recolonisation rates of ants to annual rainfall.